Language learning and identity: Positioning oneself as a language learner and user in the multilingual milieu - Lankiewicz, Hadrian; Szczepaniak-Kozak, Anna; Wąsikiewicz-Firlej, Emilia (The Spanish Society for the Study of Popular Culture SELICUP, 2014)
Identity of a language learner has recently achieved an importance of its own in academic considerations regarding the nature of language and its learning. The success of the notion in the field of language education has been triggered by poststructural or postmodern achievements in language studies on the one hand, and constructive or constructionist approaches to human learning on the other. Additionally, critical socio-cultural studies, such as the ecological approach, “assassinated” the native speaker envisaging the agency of the learner in process of personal meaning making. Concurrent language pedagogy, subsumed under the umbrella term of autonomy, tries to meet the linguistics and psychological advances, yet, as we try to demonstrate it in the present article, students find it difficult to assume new identities for themselves as legitimate users of a foreign language. A discursive analysis of an interview with students completing a semester-long sojourn in a multilingual and multicultural milieu allows us to pursue their identities pertaining to the roles of a language learner and user. Discourse as a method helps us define the normative pedagogical discourse as a dominating ideological construct positioning students’ linguistic identities and exhibiting underlying language awareness.
Keywords: identity; analysis of pedagogical discourse; Polish EFL learners; language learning; sojourn